JOURNAL "The Coustomer Satisfaction Mediation of Service Quality Its Impact on Customer Loyalty "Rumah Buby " Baby and Mom SPA, Skin, Hair and Body Care, Holistic Midwifery Care, Cimahi ". (International Journal of Psychosocial Rehabilitation, 2020)
With a customer-oriented marketing strategy, the company must understand and meet both customer behavior and needs to achieve customer satisfaction. One of the main ways to differentiate a service company is to provide higher quality services from competitors continuously. One type of company engaged in the service sector is Skin Care, Hear Treatment And Spa For Woman , Kids And Baby “Rumah Buby” service business that is different from Skin Care, Treatment And Spa For Woman , Kids And Baby “Rumah Buby” offers a different Of holistic care sensation, ranging from the physical appearance of a trendy Skin Care, Treatment And Spa For Woman , Kids And Baby attractive interior layout to offering additional facilities such as Skin Care, Hear Treatment And Spa For Woman , Kids And Baby. These additional services make the interest in hair Skin Care, Treatment And Spa For Woman , Kids And Baby business even more. Based on the above phenomenon, the authors are interested in conducting research with the title "The Mediation Effect of Customer Satisfaction in the Relationship Between Service Quality, and Sensitive Skin Care, Treatment And Spa For Woman , Kids And Baby “Rumah Buby” Customer Loyalty". Deskriptiv and verificativ is a research method with the aim of testing hypotheses that have been previously formulated (testing research). In this method there is still a descriptive explanation, but the focus still lies in explaining the relationships between variables (associative). The sample distribution of 98 customers, using Phat Analysis , Model Test (F Test), Partial Hypothesis Test (t Test). Research Results: Service quality on customer loyalty has a positive effect, the coefficient value is positive. Quality of service to customer satisfaction has a positive effect. Customer satisfaction fully mediates the effect of service quality on customer loyalty. To increase customer loyalty must further improve service quality performance in order to create customer satisfaction.